Gas Phase Polyethylene Copolymer

By using a metallocene catalyst in the gas phase polymerization method, polyethylene copolymers with a density in the range of 0.905 to 0.911 g/cm3 are prepared, which solves the problems of insufficient processability and oxygen transmission rate in the existing technology, and realizes the application suitable for Highly efficient polymers for food packaging.

CN114729080BActive Publication Date: 2025-01-24EXXONMOBIL CHEMICAL PATENTS INC
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202080079116.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-14
Filing Date
2020-11-06
Publication Date
2025-01-24
Estimated Expiration
2040-11-06

AI Technical Summary

Technical Problem

It is difficult to produce very low-density polyethylene copolymers with excellent processability and low oxygen transmittance for use in food packaging and other applications.

Method used

By using a metallocene catalyst in a gas phase polymerization method and controlling polymerization conditions such as temperature and pressure, polyethylene copolymers with densities in the range of 0.905 to 0.911 g/cm3 are prepared with excellent Dow rheology index and melt Index ratio.

Benefits of technology

The excellent machining and low oxygen through the polyethylene cluster is available for applications such as food packaging to extend the preservation period of food.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005204881900000181
    Figure GDA0005204881900000181
  • Figure GDA0005204881900000191
    Figure GDA0005204881900000191
  • Figure GDA0005204881900000211
    Figure GDA0005204881900000211
Patent Text Reader

Abstract

Polyethylene copolymers having structures that provide improved film properties are provided. The copolymers may have a molecular weight of about 0.905 to about 0.911 g / cm 3 The copolymers may also have a DRI / I2 ratio of about 0.0008 to about 0.060, an I2 value of about 0.6 to about 3.8 dg / min and an I21 value of about 8 to about 57 dg / min. Copolymers having those properties may be prepared by introducing ethylene and at least one other olefin comonomer in a comonomer / ethylene molar ratio of about 0.02 to about 0.03 into a single reactor and polymerizing at a temperature of about 76.7° C. to about 80.6° C. and a pressure of about 1,724 kPa to about 2,413 kPa. Copolymers may be used to prepare copolymers having about 150 to about 200 cc / 100 in 2 A film having an O2 permeability of 21 mol% / 24 hr and a heat tack seal initiation temperature of about 65°C to about 80°C.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Application No. 62 / 935,500, filed on November 14, 2019, entitled “Gas Phase Polyethylene Copolymers,” which is incorporated herein by reference in its entirety.

[0003] field

[0004] Embodiments of the present invention generally relate to polyethylene copolymers, and more particularly polyethylene copolymers, also referred to as very low density polyethylene (VLDPE) copolymers or plastomers, having structures that exhibit improved film properties, and to methods of making the same.

[0005] background

[0006] Polyethylene copolymers are used in a variety of products and applications. The density and flow properties of the copolymer generally determine its end use and application. The method of preparing the copolymer (whether it is solution, slurry, gas phase or other) and the catalyst system employed in the method greatly affect the density and properties of the copolymer.

[0007] In gas phase polymerization processes, for example, Ziegler-Natta ("ZN") catalysts have been able to produce low density polyethylene copolymer films that have high tensile strength, impact strength, tear resistance, film stiffness and can be drawn into thin film thicknesses. In molding applications, conventional ZN-based copolymers are known to provide excellent molding capabilities, high stiffness, fast molding cycles, and low warpage. These copolymers also typically have low taste and odor and provide excellent crack resistance and toughness over a wide temperature range. End-use applications typically include food containers, dish sinks, flip lids, and crates.

[0008] Metallocenes are known to provide low density polyethylene copolymer products with higher levels and improved property balances compared to conventional ZN-catalyzed PE copolymers. Copolymers produced by metallocene catalysts may also have outstanding toughness, clarity and improved processability compared to conventionally catalyzed copolymers. In addition, metallocene catalysts are known to have comparable polymer molecular structures, thereby allowing independent regulation of molecular weight distribution (MWD) and long chain branching.

[0009] Polyethylene copolymers with improved rheology or flow properties show better processability when extruded to form end-use products. The presence of long chain branching (LCB) in low density polymers can lead to improved flow properties. The rheological property known as the Dow Rheological Index (DRI) can be used to represent the degree of long chain branching of polymer copolymers. Another well-known rheological property is the melt flow index (MI), which measures the melting ease of thermoplastic polymers. The processability of polymer copolymers can be determined by obtaining the DRI / MI ratio. The lower the ratio, the better the balance between the long chain branching degree and the flowability of the polymer copolymer. Therefore, it is desirable to produce low density polyethylene copolymers with a lower DRI / MI ratio.

[0010] Polyethylene copolymers are particularly useful for food packaging materials. Oxygen (O2) in the air can cause food to spoil and promote the growth of aerobic microorganisms. In order to extend the shelf life of food, polyethylene copolymers that provide excellent O2 barriers are needed.

[0011] References of potential interest in this area include: KR 101740149 B1, KR 101689456 B1, US2018 / 0201705, US 6,932,592, US 6,492,475, US 6,867,277, US 7,125,946, US 7,968,659, US 8,242,220, US 8,653,193, US 9,175,119, US 9,493,591, US 9,963,525, US 10,066,036, US10,066,037.

[0012] Overview

[0013] Provided are copolymers of ethylene and at least one other comonomer and methods for preparing the same, wherein the density of the copolymer is between about 0.905 and about 0.911 g / cm 3 The copolymer exhibits very good processability as indicated by having a Dow Rheology Index (DRI) / melt index (I2) ratio of about 0.0008 to about 0.0600, a first melt index (I2) of about 0.1 to about 5.0 dg / min, and a second melt index (I21) of about 1.3 to about 90.0 dg / min. The copolymer having those properties can be prepared by introducing ethylene and at least one other comonomer in a comonomer / ethylene molar ratio of about 0.02 to about 0.03 into a single reactor and polymerizing ethylene and the other comonomer at a temperature of about 76.7° C. to about 81.1° C. and a pressure of about 1,724 kPa to about 2,413 kPa.

[0014] The foregoing copolymers can be used to prepare membranes that act as very good O2 barrier materials, such as by having a 21 mol% O2 permeability of about 150 to about 200 cc / 100 in. 2 The film also has a hot tack seal initiation temperature of about 65°C to about 80°C, which improves the quality of the film.

[0015] BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order that the manner in which the above-mentioned features of the present invention may be understood in detail, a more particular description of the invention briefly summarized above may be obtained by reference to embodiments, some of which are shown in the accompanying drawings. However, it should be noted that the accompanying drawings illustrate only typical embodiments of the present invention and are therefore not to be considered as limiting the scope thereof, as the present invention may admit to other equally effective embodiments.

[0017] Figure 1 A flow chart depicting an illustrative gas phase system that can be used in accordance with one or more embodiments provided herein.

[0018] Figure 2 is a graph of force versus temperature used during hot tack testing of one of the extruded polyethylene copolymer examples and two of the extruded comparative examples.

[0019] Figure 3 is with Figure 2 Force versus temperature plots used during hot tack testing for the same extruded polyethylene copolymer example and two different extruded comparative examples are compared.

[0020] Figure 4 is a graph of force versus temperature used during heat seal strength testing of two of the extruded polyethylene copolymer examples and the extruded comparative examples.

[0021] Figure 5 is with Figure 4 Force versus temperature graphs used during heat seal strength testing of the same extruded polyethylene copolymer example and two different extruded comparative examples are compared.

[0022] Details

[0023] It should be understood that the following disclosure describes several exemplary embodiments for implementing the different features, structures and / or functions of the present invention. The following describes exemplary embodiments of parts, arrangements and configurations to simplify the present disclosure; however, these exemplary embodiments are provided only as examples and are not intended to limit the scope of the present invention. In addition, the present disclosure can repeat figure numerals and / or letters in various exemplary embodiments and in the drawings provided herein. This repetition is for the purpose of simplicity and clarity and does not itself specify the relationship between the various exemplary embodiments and / or configurations discussed in the drawings. In addition, without departing from the scope of the present disclosure, the exemplary embodiments given below can be combined in any combination, that is, any element from one exemplary embodiment can be used in any other exemplary embodiment.

[0024] Certain terms are used throughout the following description and claims to refer to specific components. As will be appreciated by those skilled in the art, various entities may refer to the same component by different names, and thus, the naming conventions used for the elements described herein are not intended to limit the scope of the invention, which is otherwise specifically defined herein. In addition, the naming conventions used herein are not intended to distinguish between components that are named differently but function the same. In addition, in the following discussion and in the claims, the terms "including" and "comprising" are used in an open manner, and therefore should be interpreted to mean "including but not limited to". The phrase "essentially consisting of..." means that the described / claimed composition does not include any other components that would substantially change its properties by any greater than 5% of the properties, and in any case does not include any other components at a level greater than 3 weight %.

[0025] Unless otherwise indicated, all numerical values ​​are "about" or "approximately" the indicated value, meaning that the value takes into account experimental errors, machine tolerances, and other deviations that would be expected by a person of ordinary skill in the art. It should also be understood that the precise numerical values ​​used in the specification and claims constitute specific embodiments. Efforts have been made to ensure that the data are accurate in the examples. However, it should be understood that any measured data inherently contains a certain level of error due to limitations of the technology and / or equipment used to make the measurements.

[0026] The term "or" is intended to include both the exclusive and inclusive cases, ie, "A or B" is intended to be synonymous with "at least one of A and B," unless the context clearly dictates otherwise.

[0027] The indefinite articles "a" and "an" refer to both the singular (ie, "an") and the plural (ie, one or more), unless the context clearly dictates otherwise.

[0028] Each of the appended claims defines a separate invention, which, for infringement purposes, is deemed to include equivalents to the various elements or limitations specified in the claims. Depending on the context, all references to the "invention" may refer to only certain specific embodiments in some cases. In other cases, it will be understood that references to the "invention" will refer to one or more of the subject matter recited in the claims, but not necessarily all of them. Each invention will now be described in more detail below, including specific embodiments, forms, and examples, but the invention is not limited to these embodiments, forms, or examples, which, when the information in this disclosure is combined with publicly available information and technology, are included to enable one of ordinary skill in the art to make and use the invention.

[0029] Disclosed herein are low density copolymers of ethylene and one or more other olefins (also referred to as "polyethylene copolymers") having significantly improved physical properties. The copolymers may have a density of about 0.905 to about 0.912 g / cm3 (g / cm 3 ), preferably in the range of about 0.907 to about 0.911 g / cm 3 and most preferably in the range of about 0.908 to about 0.910 g / cm 3 As used herein, "about" in the context of density may include + / - 0.001 g / cm 3 (For example, a density of 0.905 can include 0.904-0.906 in some embodiments). Polyethylene copolymers can also have a first melt index (I2) value of about 0.1 to about 5.0 decigrams / minute (dg / min), preferably about 0.4 to about 3.4dg / min and most preferably about 1.4 to 2.4dg / min. Polyethylene copolymers can also have a second melt index (I21) value of about 1.3 to about 90.0dg / min, preferably about 5.0 to about 60.0dg / min and most preferably about 18.0 to about 43.0dg / min. Copolymers can also have a DRI / I2 ratio in the range of about 0.0008 to about 0.0600, preferably in the range of about 0.001 to about 0.060 and more preferably in the range of about 0.007 to about 0.028. Surprisingly and unexpectedly found that the low density polyethylene copolymers described herein show improved processability compared to other low density polyethylene copolymers.

[0030] Advantageously, films made from the polyethylene copolymers described herein have significantly improved properties. According to various embodiments, a film having a thickness of about 1 mi l may have a 21 mole (mol) % O2 permeability of about 150 to about 200 cubic centimeters per 100 square inches per 24 hours (cc / 100 in2). 2 / 24hr). The 21mol% O2 permeability of 1mil membrane may preferably be about 160 to about 200cc / 100in 2 / 24 hours and more preferably in the range of about 170 to about 190 cc / 100 in 2 In the range of / 24hr. The film with such low O2 permeability can form a good O2 barrier material and can therefore be used in food packaging to help extend the shelf life of food. In other embodiments, the film can also have a heat tack seal initiation temperature of less than about 85°C, preferably less than about 80°C and more preferably less than about 75°C. In another embodiment, the film can have a heat tack seal initiation temperature in the range of about 65°C to about 80°C, preferably in the range of about 67°C to about 78°C and more preferably in the range of about 70°C to about 75°C. The ability to use a lower seal initiation temperature during package formation advantageously leads to improved packaging quality.

[0031] As described herein, copolymers of ethylene and one or more other olefins may be or may include one or more copolymers having ethylene-derived monomer units and one or more other olefin comonomer units, including terpolymers. The amount of ethylene-derived units in the copolymer may range from a lower limit of about 92.5 mol% or 93.0 mol% to an upper limit of about 97.5 mol%, 97.0 mol% or 96.8 mol%. In addition, the amount of comonomer-derived units in the copolymer may range from a lower limit of about 2.50 mol%, about 3.00 mol% or about 3.25 mol% to an upper limit of about 7.50 mol%, about 7.00 mol% or about 6.75 mol%. The aforementioned mole percentages are based on the total amount of ethylene-derived units and comonomer-derived units.

[0032] Examples of suitable comonomers include α-olefins such as C3-C 20 α-olefins or C3-C 12 α-olefins. The α-olefin comonomers may be linear or branched, and two or more comonomers may be used if desired. Examples of suitable comonomers include linear C3-C 12α-olefins and α-olefins with one or more C1-C3 alkyl branches or aryl groups. Specific examples include, but are not limited to, propylene; 3-methyl-1-butene; 3,3-dimethyl-1-butene; 1-pentene; 1-pentene with one or more methyl, ethyl or propyl substituents; 1-hexene with one or more methyl, ethyl or propyl substituents; 1-heptene with one or more methyl, ethyl or propyl substituents; 1-octene with one or more methyl, ethyl or propyl substituents; 1-nonene with one or more methyl, ethyl or propyl substituents; 1-decene substituted with ethyl, methyl or dimethyl; 1-dodecene; and styrene. Preferred comonomers include propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-octene and styrene. A particularly preferred comonomer is 1-hexene.

[0033] The Dow Rheology Index (DRI) described above was developed by S Lai and GW Knight to characterize the rheological properties of substantially linear ethylene polymers (ANTEC '93 Proceedings, Inst. TM Technology Polyolef ins (ITP) - New Rules in the Structure / Rheology Relationship of Ethylene & -01ef in Copolymers, New York, La., May 1993). It represents the "normalized relaxation time as a result of long chain branching" of a polymer. In S. Lai et al. (ANTEC '94, Dow Rheology Index (DRI) for Ins i te TM In Dow's Technology Polyolefins (ITP): Unique Structure-Processing Relationships, pp. 1814-1815), DRI is defined as the degree to which the rheology of an ethylene-octene copolymer incorporating long chain branches into the polymer backbone, referred to as ITP (Dow's Information Technology Polyolefins), deviates from the rheology reported as a conventional linear homogeneous polyolefin without long chain branches (LCB), as shown by the following normalized equation:

[0034] DRI = [365000 (τ0 / η ο )-IJ / 10]

[0035] Where τ0 is the characteristic time relaxation of the material and is the zero shear rate complex viscosity of the material. The DRI is calculated by least squares fitting of the rheological curve (dynamic complex viscosity η*(ω) versus applied frequency (CO), e.g., 0.01 to 100 rads / sec) using the following generalized Cross equation, as described in U.S. Pat. No. 6,114,486, which is incorporated herein by reference in its entirety:

[0036] η*(ω)=η ο / [1+(ω·τ ο ) η ]

[0037] Where η is the power law index of the material, η*(ω) and CO are the measured complex viscosity and applied frequency data, respectively. Dynamic rheology measurements are performed in a dynamic rheometer (e.g., ARES Rheometer from TA Instruments) using 25 mm diameter parallel plates in dynamic mode under an inert atmosphere according to ASTM D 4440. More details on how to determine DRI can be found in U.S. Pat. No. 9,175,119, and in particular, column 13, line 56 to column 15, line 12, which description is incorporated herein by reference in its entirety.

[0038] The melt flow index mentioned above can be obtained by measuring the mass of the polyethylene copolymer flowing through a capillary of a specific diameter and length in ten minutes for a selected specified temperature via a pressure applied by a load of a specified weight, and is expressed in grams of polymer per 10 minutes of test duration. MI2 refers to ASTM D 1238 (190°C / 2.16kg) and MI21 refers to ASTM D 1238 (190°C / 21.6kg).

[0039] "Hot tack seal initiation temperature" refers to the temperature at which the hot tack strength is at least 8N according to the hot tack test of ASTM F1921 (method B). In the hot tack test, the film sample is heated to a given temperature and pressed (sealant side to sealant side); the force required to pull the film apart at a given temperature is measured and recorded as the hot tack strength. In addition, the hot seal test can confirm the seal initiation temperature as determined by the hot tack test. The hot seal test includes heat-sealing the film sample at a given temperature, then conditioning at about room temperature, then pulling the seal apart and measuring the force required to pull the seal apart. The force to pull the seal apart is plotted against the temperature at which the seal is formed (before conditioning). More details of these tests can be found in Table 8 (Test Procedure).

[0040] Film provided herein can be monolayer or multilayer film.In one embodiment, film can include at least one layer, whether it is the only layer of monolayer film or the layer of multilayer film, it comprises about 5 weight %-about 95 weight % based on ethylene copolymer, based on the gross weight of film layer.Preferably, the film layer has a thickness of about 7 microns (μm) to about 200 μm, and more preferably 10 μm to about 150 μm, and more preferably 10 μm to about 100 μm, and more preferably 20 μm to about 90 μm, and more preferably 15 μm to about 75 μm.If it is a part of a multilayer film structure, the film layer accounts for at least about 5% of the total film thickness, or at least 10%, or at least 15%, or at least 17%, or at least 20%, or at least 22% of the total film thickness.

[0041] To facilitate discussion of different multilayer film structures, each layer of the film may be represented by a different letter, such as A, B, C, D, E, etc., depending on the number of different layers. When the film includes more than one layer, such as more than one A layer, one or more primes (', ", "', etc.) are appended to the A symbol (i.e., A', A", etc.) to represent the same type of layers (conventional or inventive), which may be the same or may differ in one or more properties such as chemical composition, density, melt index, thickness, etc., which are within the range of these parameters defined herein. Finally, the symbols of adjacent layers are separated by a slash ( / ). Using this notation, a three-layer film may be represented as A / B / A or A / C / A. Similarly, a five-layer film of alternating conventional / inventive layers would be represented as A / B / A' / B' / A". Unless otherwise indicated, the order of the layers from left to right or right to left is not significant, nor is the order of the primes; for example, an A / B film is equivalent to a B / A film, and an A / A' / B / A" film is equivalent to an A / B / A' / A" film. When a multilayer film has two or more identical layers, such as two or more B layers, for example, the B layers can be identical or can differ in thickness, chemical composition, density, melt index, CDBI, MWD, additives used, or other properties.

[0042] In at least one specific embodiment, the film is an A / B / A multilayer film, wherein each "A" layer ("skin layer") is the same or different and is located on either side of a "B" layer ("core layer"). The thickness ratio of the core layer to the skin layer is generally preferably in the range of 1 / 1 / 1-1 / 4 / 1, more preferably 1 / 1.5 / 1-1 / 3 / 1, even more preferably 1 / 1.5 / 1-1 / 2.5 / 1, and most preferably the ratio of the core layer to the skin layer will be 1 / 2 / 1, wherein the first and third numbers are understood to represent the skin layers and the middle numbers represent the core layer.

[0043] The thickness of each layer and the total film thickness are not particularly limited, but are determined according to the desired film properties. Each film layer may have a thickness of about 1 to 1,000 microns (μm), more typically about 5 to 100 μm. Those skilled in the art will appreciate that the thickness of a single layer of a multilayer film can be adjusted based on desired end-use performance, the resin or copolymer used, equipment capabilities, and other factors.

[0044] The typical total thickness of the multilayer film may range from about 10 to about 100 μm. In one or more embodiments, the total film thickness may range from about 0.5 μm to about 250 μm. In one or more embodiments, the total film thickness may range from a lower limit of 10, 50, or 100 μm to an upper limit of about 120, 150, or 200 μm. In one or more embodiments, the total film thickness may range from about 25 μm to about 50 μm.

[0045] For example, the multilayer film can have an optical film gauge of about 0.1 mil to about 70 mil, about 0.3 mil to about 55 mil, about 0.5 mil to about 30 mil, or about 1 mil to about 10 mil, where "mil" is known in the art as one thousandth of an inch. Optical film thickness can be measured using any method or device known in the art, such as a laser micrometer. For example, optical film thickness can be measured using a Beta LaserMike Model 283-20 ​​available from Beta LaserMike USA.

[0046] In one or more embodiments, multilayer films having any of the following illustrative structures may be used:

[0047] (a) two-layer films, such as A / B and B / B';

[0048] (b) three-layer films, such as A / B / A', A / A' / B, A / B / B', B / A / B', B / B' / B", A / B / A and A / C / A;

[0049] (c) Four-layer films, such as A / A' / A" / B, A / A' / B / A", A / A' / B / B', A / B / A' / B', A / B / B' / A', B / A / A' / B', A / B / B' / B", B / A / B' / B" and B / B' / B" / B"';

[0050] (d) Five-layer film, such as A / A' / A" / A"' / B, A / A' / A" / B / A"', A / A' / B / A" / A"', A / A' / A" / B / B', A / A' / B / A" / B ', A / A' / B / B' / A", A / B / A' / B' / A", A / B / A' / A" / B, B / A / A' / A" / B', A / A' / B / B' / B", A / B / A' / B' / B", A / B / B' / B" / A', B / A / A' / B' / B", B / A / B' / A' / B", B / A / B' / B" / A', A / B / B' / B" / B"', B / A / B' / B" / B"', B / B' / A / B" / B"', B / B' / B" / B"', B / B' / B" / B"' / B" and A / B / C / B / A; and similar structures for films having six, seven, eight, nine or more layers. It will be appreciated that films having still more layers can be used.

[0051] Figure 1 A flow chart depicting an illustrative gas phase system 200 that can be used to prepare the polyethylene copolymers disclosed herein. System 200 may include a single reactor 240 in fluid communication with one or more blowdown tanks 255 (only one shown), buffer tanks 260 (only one shown), recycle compressors 270 (only one shown), and heat exchangers 275 (only one shown). For simplicity and ease of description, embodiments of the invention will also be described in the context of a single reactor train.

[0052] In one or more embodiments, the reactor 240 can include a reaction zone 245 in fluid communication with a velocity reduction zone 250. The reaction zone 245 can include a bed of growing polymer particles, formed polymer particles, and catalyst particles fluidized by continuous flow of polymerizable and modifying gaseous components through the reaction zone 245 in the form of make-up feed and recycle fluid.

[0053] The feed stream or make-up stream 210 may be introduced into the polymerization system at any point. For example, the feed stream or make-up stream 210 may be introduced into the reactor fluidized bed in the reaction zone 245 or into any point within the expansion section 250 or the recycle stream 215. Preferably, the feed stream or make-up stream 210 is introduced into the recycle stream 215 before or after the heat exchanger 275. Figure 2 In FIG. 1 , feed stream or make-up stream 210 is depicted as entering recycle stream 215 after heat exchanger (“cooler”) 275 .

[0054] The term "feed stream" as used herein refers to the raw materials for producing the polyethylene copolymer described herein in the polymerization process. The feed stream may include ethylene monomer and one or more olefin comonomers, including but not limited to substituted and unsubstituted olefins with 3 to 20 carbon atoms, more preferably 3 to 12 carbon atoms. The example of such comonomers includes but is not limited to propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, styrene and their derivatives, wherein 1-hexene is preferred. The feed stream may also include non-olefin gases such as nitrogen and hydrogen. In one or more embodiments, the feed stream may have an olefin comonomer / ethylene monomer molar ratio of about 0.02-about 0.03, preferably about 0.024-about 0.032, more preferably about 0.026-about 0.032. As used herein, the term "about" in the context of comonomer / ethylene monomer molar ratio can include a range of + / -0.005 (e.g., so that about 0.024 can be included in a molar ratio within the range of 0.0235-0.0245 in some embodiments). The feed stream can enter the reactor at multiple and different locations. For example, monomers can be introduced into the polymerization zone by direct injection into the bed through a nozzle (not shown in the figure) in various ways. The feed stream can also include one or more non-reactive alkanes, which can be condensed during the polymerization process for removing reaction heat. Illustrative non-reactive alkanes include, but are not limited to, propane, butane, isobutane, pentane, isopentane, hexane, their isomers and their derivatives. It should be noted that in practice, the molar ratio of the comonomer / monomer provided to the reactor can be measured in some cases by measuring the molar ratio in the vapor tower overhead in the reactor. In the event of any difference between (i) the molar ratio determined based on the feed stream measurement and (ii) the molar ratio determined based on the measurement of the gas overhead in the reactor, the molar ratio as determined based on the measurement of the gas overhead in the reactor shall prevail, and such ratio shall be considered the molar feed ratio for purposes of this disclosure.

[0055] The fluidized bed may have the general appearance of densely packed moving particles resulting from the permeation of gas through the bed. The pressure drop through the bed is equal to or slightly greater than the weight of the bed divided by the cross-sectional area. It therefore depends on the geometry of the reactor. In order to maintain a viable fluidized bed in reaction zone 245, the superficial gas velocity through the bed must exceed the minimum flow required for fluidization. Preferably, the superficial gas velocity is at least twice the minimum flow velocity. Typically, it is sufficient for the superficial gas velocity to be no more than 1.52 m / sec and often no more than 0.762 m / sec.

[0056] In general, the height to diameter ratio of reaction zone 245 can vary in the range of about 2: 1 to about 5: 1. Of course, this range can vary to greater or lesser ratios and depends on the desired production capacity. The cross-sectional area of ​​velocity reduction zone 250 is typically in the range of about 2 to about 3 times the cross-sectional area of ​​reaction zone 245.

[0057] The velocity reduction zone 250 may have a larger inner diameter than the reaction zone 245. As the name implies, the velocity reduction zone 250 may slow the velocity of the gas due to the increased cross-sectional area. This reduction in gas velocity may allow particles entrained in the upwardly moving gas to fall back into the bed, primarily allowing the gas to exit the top of the reactor 240 only through the recycle gas stream 215.

[0058] The recycle stream 215 can be compressed in the compressor 270 and then passed through the heat exchanger 275 (wherein heat is removed) and then returned to the bed. The heat exchanger 275 can be of horizontal or vertical type. If necessary, several heat exchangers can be used to reduce the temperature of the circulating gas flow in the stage. The compressor can also be positioned downstream of the heat exchanger or at an intermediate point between several heat exchangers. After cooling, the recycle stream 215 can be returned to the reactor 240. The cooled recycle stream can absorb the reaction heat generated by the polymerization reaction. In one or more of the above or other embodiments herein, a compression mode operation can be used, such as described in U.S. Patent Nos. 4,543,399, 4,588,790, 5,352,749 and 5,462,999, to help remove heat from the reactor 240.

[0059] In one or more embodiments, the recycle stream 215 can be returned to the reactor 240 and to the fluidized bed through the gas distributor plate 280. A gas baffle 285 is preferably installed at the inlet of the reactor to prevent the contained polymer particles from settling out and agglomerating into solid matter, and also to prevent liquid from accumulating at the bottom of the reactor to facilitate easy conversion between processes containing liquid and processes without liquid in the recycle gas stream, and vice versa. Illustrative baffles suitable for this purpose are described in U.S. Pat. Nos. 4,933,149 and 6,627,713.

[0060] The catalyst or catalyst system can be introduced into the fluidized bed in the reactor 240 through one or more injection nozzles 230. The catalyst or catalyst system is preferably introduced as preformed particles (i.e., catalyst slurry) in one or more liquid carriers. Suitable liquid carriers include mineral oils and liquid hydrocarbons, including but not limited to propane, butane, isopentane, hexane, heptane and octane, or mixtures thereof. Gases inert to the catalyst slurry, such as nitrogen or argon, can also be used to bring the catalyst slurry into the reactor 240. In one or more embodiments, the catalyst or catalyst system may be a dry powder. In one or more embodiments, the catalyst or catalyst system may be dissolved in a liquid carrier and introduced into the reactor 240 as a solution.

[0061] When discharging the particulate polymer product from the reactor 240, it is desirable and preferred to separate the fluid from the product and return the fluid to the recycle line 215. In one or more embodiments, this separation can be accomplished when the fluid and product exit the reactor 240 and enter the product discharge tank 255 (one shown) through valve 257, which can be a ball valve designed to have minimal flow restriction when open. Conventional valves 259 and 267 can be located above and below the product discharge tank 255. Valve 267 can allow the product to enter the product buffer tank 260 (only one shown).

[0062] In at least one embodiment, to discharge the granular polymer from the reactor 240, valve 257 may be opened while valves 259 and 267 are in the closed position. The product and fluid may enter the product discharge tank 255. Valve 259 may be opened to allow the fluid to return to the reactor 240. Valve 257 may be closed, allowing the product to settle in the product discharge tank 255. Valve 259 may then be closed. Valve 267 may be opened and any product in the product discharge tank 255 flows into the product buffer tank 260. Valve 267 may then be closed. The product may then be discharged from the product buffer tank 260 through valve 264. The product may be further purged via purge stream 263 to remove residual hydrocarbons (and vented at 262) and transported to a pelletizing system or storage (not shown). The specific timing sequence of valves 257, 259, 267, and 264 may be accomplished by using conventional programmable controllers well known in the art.

[0063] Another preferred product discharge system that may be used alternatively is disclosed and claimed in U.S. Pat. No. 4,621, 952. Such a system uses at least one pair of (parallel) tanks comprising a settling tank and a transfer tank arranged in series and having a separated gas phase returned from the top of the settling tank to a point in the reactor near the top of the fluidized bed.

[0064] The fluidized bed reactor may be equipped with an appropriate exhaust system (not shown) to allow the bed to be vented during startup and shutdown. The reactor need not employ agitation and / or scraped walls. The recycle line 215 and the elements therein (compressor 270 and heat exchanger 275) may be smooth-surfaced and free of unnecessary obstructions so as not to impede the flow of the recycle fluid or entrained particles.

[0065] In one or more embodiments, the polymerization conditions used in the method for preparing the polyethylene copolymer described herein can be selected to achieve the desired improved properties of the copolymer. More specifically, the temperature can be in the range of about 74°C, 75°C, 75.56°C, 76.7°C or 77.2°C lower limits to about 80.0°C, 80.6°C or 81.1°C upper limits, wherein the range from any of the aforementioned lower ends to any of the aforementioned upper ends is also encompassed (e.g., about 76.7°C to about 81.1°C, about 76.7°C to about 80.6°C, or 77.2°C to about 80.0°C in various embodiments). In some embodiments, the temperature can be in the range of about 75.56°C-about 80°C. As used herein with respect to temperature, "about" may include + / -1°C, so that in various embodiments, for example, a temperature of 75.56°C may include 74.56-76.56°C. The pressure may be in the range of about 1,724 kilopascals (kPa) to about 2,413 kPa, preferably in the range of about 1,931 kPa to about 2,068 kPa, and more preferably in the range of about 1,965 kPa to about 2,034 kPa. Additional details of polymerization may be found in U.S. Pat. No. 6,627,713, which is incorporated by reference at least to the extent that it discloses polymerization details.

[0066] The catalyst system may include Ziegler-Natta catalysts, chromium-based catalysts, metallocene catalysts, and other single-site catalysts, including Group 15-containing catalysts, bimetallic catalysts, and mixed catalysts. The catalyst system may also include AlCl3, cobalt, iron, palladium, chromium / chromium oxide, or a "Phi ll ips" catalyst. Any catalyst may be used alone or in combination with the others.

[0067] The term "catalyst system" includes at least one "catalyst component" and at least one "activator", or at least one co-catalyst. The catalyst system may also include other components such as a carrier, and is not limited to the catalyst components and / or activators alone or in combination. The catalyst system may include any number of the catalyst components in any combination, and any activator in any combination.

[0068] The term "catalyst component" includes any compound capable of catalyzing the polymerization or oligomerization of olefins once suitably activated. Preferably, the catalyst component may include at least one Group 3 to Group 12 atom and optionally at least one leaving group associated therewith.

[0069] The term "leaving group" refers to one or more chemical moieties bound to the metal center of a catalyst component that can be abstracted from the catalyst component by an activator, thereby producing a species active for olefin polymerization or oligomerization. Suitable activators are described in detail below.

[0070] As used herein, with respect to “Groups” of the Periodic Table elements, the “new” numbering scheme for Periodic Table Groups as in the CRC Handbook of Chemistry and Physics (David R. Lide, ed., CRC Press, 81st ed., 2000) is used.

[0071] The term "substituted" means that the group following the term has at least one structural part replacing one or more hydrogens at any position, the structural part is selected from, for example, the following groups: halogen groups (e.g., Cl, F, Br), hydroxyl groups, carbonyl groups, carboxyl groups, amine groups, phosphine groups, alkoxy groups, phenyl groups, naphthyl groups, C1-C7 alkyl groups, C2-C7 alkenyl groups, and combinations thereof. Examples of substituted alkyl and aryl groups include, but are not limited to, acyl groups, alkylamino groups, alkoxy groups, aryloxy groups, alkylthio groups, dialkylamino groups, alkoxycarbonyl groups, aryloxycarbonyl groups, carbamoyl groups, alkyl- and dialkyl-carbamoyl groups, acyloxy groups, acylamino groups, arylamino groups, and combinations thereof.

[0072] According to one embodiment, the catalyst may include one or more metallocene catalyst components, also referred to as "metallocenes". Suitable metallocenes are generally described in 1 & 2 Metallocene-Based Polyolef ins (John Scheirs & W. Kaminsky, ed., John Wiley & Sons, Ltd. 2000), GG Larky, 181 Coordination Chem. Rev. 243-296 (1999) and are particularly useful for use in the synthesis of polyethylene, described in 1 Metallocene-Based Polyolef ins 261-377 (2000), each of which is incorporated herein in its entirety. The metallocene catalyst compounds as described herein may include one or more Cp ligands (cyclopentadienyl and isolobal ligands) bonded to at least one Group 3 to Group 12 metal atom, and "half-sandwich" and "full-sandwich" compounds bonded to one or more leaving groups of at least one metal atom. One particularly suitable metallocene is a zirconocene containing a carbon-zirconium bond, which is available from Univation Technologies, LLC under the trade name XCAT TMCommercially available. In one embodiment, the metallocene catalyst component may be supported on a support material and may be supported with or without another catalyst component.

[0073] The Cp ligand may be one or more rings or ring systems, at least a portion of which includes a π-bonded system, such as cyclodienyl ligands and heterocyclic analogs. The ring(s) or ring system(s) typically include atoms selected from the following: atoms from Groups 13 to 16, or the atoms constituting the Cp ligand are selected from the following: carbon, nitrogen, oxygen, silicon, sulfur, phosphorus, germanium, boron and aluminum and combinations thereof, wherein carbon accounts for at least 50% of the ring members. Alternatively, the Cp ligand(s) may be selected from the following: substituted and unsubstituted cyclopentadienyl ligands and ligands isolobal to the cyclopentadienyl group, non-limiting examples of which include cyclopentadienyl, indenyl, fluorenyl and other structures. Additional non-limiting examples of such ligands include cyclopentadienyl, cyclopentaphenanthryl, indenyl, benzindenyl, fluorenyl, octahydrofluorenyl, cyclooctatetraenyl, cyclopentacyclododecene, phenanthroindenyl, 3,4-benzofluorenyl, 9-phenylfluorenyl, 8-H-cyclopent[a]acenaphthylenyl, 7H-dibenzofluorenyl, indeno[1,2-9]anthrene, thienoindenyl, thienofluorenyl, hydrogenated versions thereof (e.g., 4,5,6,7-tetrahydroindenyl or "H4Ind"), substituted versions thereof, and heterocyclic versions thereof.

[0074] Film can be formed by any number of known lamination, extrusion or coextrusion techniques. Any commonly used blown film, tenter film or cast film technology is suitable. For example, in the cast film process, the resin composition can be molten state through a flat die extruded and then cooled to form a film. Alternatively, the composition can be molten state through an annular die extruded and then blown and cooled to form a tubular blown film, which can then be used to prepare a bag or cut and unfolded to form a flat film.

[0075] The extrusion temperature, die temperature and chill roll temperature are independent of the composition of the polymer composition employed, but will generally be within the following ranges for the compositions described herein: extrusion temperature 170° C. to 250° C.; die temperature 170° C. to 250° C.; and chill roll temperature 10° C. to 65° C. The film making process may also include an embossing roll to cool and form the film.

[0076] The film can also be unoriented, uniaxially oriented or biaxially oriented. In one or more embodiments, the multilayer film can be uniaxially or biaxially oriented. Orientation in the extrusion direction is referred to as longitudinal (MD) orientation. Orientation perpendicular to the extrusion direction is referred to as transverse (TD) orientation. Orientation can be accomplished by first stretching or pulling the film in MD and then TD orientation. Blown film or cast film can also be oriented again in one or two directions by the subsequent tenter frame orientation of the film extrusion process. Orientation can be sequential or simultaneous, depending on the desired film characteristics. For example, the orientation ratio can be about three to about six times the extrusion width in the longitudinal direction and about four to about ten times the extrusion width in the transverse direction. Typical commercial orientation processes are BOPP tenter frame processes and blown films.

[0077] In a specific film orientation embodiment, a cross-grooved roll assembly is used to simultaneously produce the desired corrugated surface roughness and orient the film. Such a process is described in U.S. Pat. No. 4,368,565. In this process, the film is stretched between two interlocking grooved rolls that are capable of biaxially stretching the film and orienting it.

[0078] For multilayer films, the materials forming each layer can be coextruded through a coextrusion feed block and die assembly to produce a film having two or more layers adhered together but of different composition. Coextrusion can be applied to cast film or blown film processes. Multilayer films can also be formed by combining two or more monolayer films using conventional lamination techniques. Example:

[0079] The foregoing discussion may be further described with reference to the following non-limiting examples.

[0080] Polyethylene copolymers (Examples E1, E2, E3, E4, E5 and E6) according to one or more embodiments described herein are produced by feeding 1-hexene (C6) and ethylene (C2) to a single gas phase reactor at the C6 / C2 molar ratio shown in Table 1 below. Table 1 also describes the process conditions used to form Examples E1-E6. The feed stream also includes hydrogen (H2), nitrogen (N2) and isopentane (iC5) in the amounts shown in Table 1. The fluidized catalyst bed is introduced into a reactor containing XCAT TM The reactor of the zirconocene catalyst. The polymerization bed temperature range for the production examples was 168°F (75.56°C) - 176.0°F (80°C). In addition, the reactor pressure range was 290.0 psig - 299.7 psig. The production rate, catalyst productivity and percentage of the product stream compressed are also given in Table 1.

[0081] Table 1: Process conditions of Examples E1-E6

[0082] E1 E2 E3 E4 E5 E6 Bed temperature °F 176 170 176.1 168.0 172.0 172 Reactor pressure PsiG 299.5 299.7 290.0 290.0 290.0 290 Ethylene concentration mol% 69.95 70.02 60.55 67.02 57.20 56.9 <![CDATA[H2 concentration]]> ppm 169 166 102.3 359.9 235.0 235 <![CDATA[C6 / C2 = gas ratio]]> mol / mol 0.0316 0.0400 0.0260 0.0263 0.0297 0.0312 iC5 Composition mol% 0 0 2.53 0.0 5.9 5.7 <![CDATA[Composition of N2]]> mol% 27.8 27.2 35.68 30.4 36.3 36.3 Production rate lb / hr 163 124 65.1 82.8 63000.0 58960 Catalyst productivity lb / lb 10501 15109 6998.8 9183 8581.0 8581 %Compressed weight% 0 0 0 0 8.0 6.4

[0083] Table 2 below shows the process conditions for the production of a comparative example of a polyethylene copolymer which was further processed in the same manner as the examples shown in Table 1 (see description below). Example C1 is Exceed sold by Exxon Mobil Corporation. TM 1012; Examples C3 and C4 were prepared in-house; Example C5 was sold by Exxon Mobil Corporation. TM 1018; Example C6 is Exceed sold by Exxon Mobile Corporation TM 3518 and Example C 12 Exceed is sold by Exxon Mobile Corporation TM 2012.

[0084] Table 2: Comparative Examples C1, C3, C4, C5, C6 and C 12 Process conditions

[0085] <![CDATA[C1]]> <![CDATA[C3]]> <![CDATA[C4]]> <![CDATA[C5]]> <![CDATA[C6]]> <![CDATA[C 12 ]]> Bed temperature °F 176.0 191.0 191.0 185.0 185.0 176.0 Reactor pressure PsiG 290.0 290.0 289.9 290.0 290.0 290.0 Ethylene concentration mol% 60.63 66.81 66.92 67.21 64.02 58.72 <![CDATA[H2 concentration]]> ppm 191 205.6 69.5 199 376 259 <![CDATA[C6 / C2 = gas ratio]]> mol / mol 0.0280 0.0132 0.0102 0.0297 0.0256 0.0273 iC5 Composition mol% 10.7 3.16 2.85 16.7 15.6 9.7 <![CDATA[Composition of N2]]> mol% 23.8 29.55 30.21 15.64 19.60 30.09 Production rate lb / hr 89100 64.8 49.6 96900 113000 84800 Catalyst productivity lb / lb 6085 5157 3128 6440 6958 8118 %Compressed weight% 16.5 0 0 20.6 23.4 13.0

[0086] The polyethylene copolymer examples (E1-E6) and various comparative examples (C1, C2, C3, C4, C5, C6, C7, C8, C9, C10, C11, C12, C13, C14, C15, C16, C17, C18, C19, C20, C21, C22, C23, C24, C25, C26, C27, C28, C29, C30, 10 , C 11 , C 12 and C 13 ) and then conditioned for 40 hours according to ASTM D618-08 before testing. As shown in Tables 3 and 4 below, the density of the examples was also measured according to ASTM D1505. Examples C1, C3, C4, C5, C6 and C7 have been provided above. 12 In addition, Example C2 is Exact sold by Exxon Mobile Corporation. TM 3132; Example C7 is Evolue sold by Prime Polymer Co., Ltd. TM SP0510; Example C8 is Evolue sold by Prime Polymer Co., Ltd. TM SP1510; Example C9 is Evolue sold by Prime Polymer Co., Ltd. TM SP1520; Example C 10 Eli Te sold by Dow Chemical Company TM5400; Example C 11 Dowlex is sold by Dow Chemical Company TM ; and Example C 13 Affinity sold by Dow Chemical Company TM PL1880G.

[0087] In addition, I2 and I21 melt flow values ​​were measured according to ASTM D1238 for each of the examples shown in Tables 3, 4, and 5. Some examples (E1-E6 and C1-C 11 ) DRI and DRI / I2 values. As shown in Table 3, it was found that the DRI / I2 ratio of Examples E1, E2, E4, and E5 ranged from 0.007 to 0.028, which is good for having a density between 0.9036 and 0.9099 g / cm 3 Thus, the inventive examples exhibit very good extrusion processability.

[0088] As also shown in Tables 3, 4 and 5, the number average molecular weight (Mn), weight average molecular weight (Mw), size average molecular weight (Mz), and molecular weight distribution (Mw / Mn and Mz / Mw) and complex viscosity were determined for the following examples: E1-E5 and C1-C 11 See Table 8 below for a description of how the molecular weight and complex viscosity values ​​are determined.

[0089] Table 3: Composition of matter of Examples E1-E6

[0090] E1 E2 E3 E4 E5 E6 <![CDATA[I2]]> dg / min 1.1 1.01 0.53 3.35 1.9 1.9 <![CDATA[I 21 ]]> dg / min 17.56 16.66 8.9 57.8 30.9 31.4 MFR 16.8 16.8 16.7 17.3 16.3 16.5 density g / cc 0.9099 0.9036 0.9066 0.9057 0.9093 0.9094 Mn Dalton 61450 62230 50228 29852 34144 M Dalton 117151 124029 126520 76780 88823 Mz Dalton 184120 197222 230811 136861 159431 Mw / Mn 1.91 1.99 2.52 2.57 2.60 Mz / Mw 1.57 1.59 1.82 1.78 1.79 <![CDATA[Eta*10 2 ]]> Pa*s 2454 2457 3270 1240 1798 <![CDATA[Eta*10 1 ]]> Pa*s 5151 5394 8605 1976 3255 <![CDATA[Eta*10 0 ]]> Pa*s 6469 6932 12709 2206 3802 <![CDATA[Eta*10 -1 ]]> Pa*s 6791 7319 14034 2252 3919 DRI 0.019 0.028 0.045 0.025 0.017 <![CDATA[DRI / I2]]> 0.017 0.028 0.084 0.007 0.009 Comonomer Hexene Hexene Hexene % Ethylene mol% 94.3 93.7 95.0 % comonomer mol% 5.7 6.3 5.0

[0091] Table 4: Composition of matter of Comparative Examples C1-C7

[0092]

[0093]

[0094] Table 5: Comparative Examples C8-C 13 Composition of matter

[0095] <![CDATA[C8]]> <![CDATA[C9]]> <![CDATA[C 10 ]]> <![CDATA[C 11 ]]> <![CDATA[C 12 ]]> <![CDATA[C 13 ]]> <![CDATA[I2]]> dg / min 0.88 1.96 1.02 1.03 1.91 1.05 <![CDATA[I 21 ]]> dg / min 15.6 30.7 30.5 29.8 30.3 31.2 MFR 17.7 15.6 29.9 28.9 15.9 29.7 density g / cc 0.9127 0.9129 0.9164 0.9215 0.9118 0.9065 Mn Dalton 33395 34349 27324 25796 M Dalton 112009 87704 100105 112063 Mz Dalton 220670 158012 253852 433373 Mw / Mn 3.35 2.55 3.66 4.34 Mz / Mw 1.97 1.80 2.54 3.87 <![CDATA[Eta*10 2 ]]> Pa*s 2419 1755 1533 1593 <![CDATA[Eta*10 1 ]]> Pa*s 5672 3074 3954 4146 <![CDATA[Eta*10 0 ]]> Pa*s 7675 3549 7758 7135 <![CDATA[Eta*10 -1 ]]> Pa*s 8239 3650 11062 8791 DRI 0.055 0.012 1.469 0.505 <![CDATA[DRI / I2]]> 0.062 0.006 1.441 0.491 Comonomer Hexene Hexene Octene Octene % Ethylene mol% 95.9 96.3 96.7 97.2 % comonomer mol% 4.1 3.7 3.3 2.8

[0096] Polyethylene copolymer Examples E5 and E6 and Comparative Examples C2, C7, C 12 and C 13Further extruded into 1mil monolayer films. Polymerized blown film evaluations were performed on an Alpine blown film line equipped with a 160mm monolayer die with a 90mil die gap and a 2.5:1 BUR. Table 6 below provides details of the blown film process conditions. For each of the above examples, individual film properties were measured in the machine direction (MD) and the transverse direction (TD). More specifically, these properties are Elmendorf tear strength, dart impact, secant modulus, tensile strength, yield strength, elongation at break, haze and gloss. The values ​​of all these properties are described in Table 7 below. Table 8 below names or describes the test methods used to obtain all the properties provided in the table. The films of Examples E5 and E6 are better than those of Comparative Examples C2, C7 and C 13 The films of Example E5 and E6 have higher Elmendorf tear strength, secant modulus, tensile energy, yield strength and elongation. Comparison of those film properties of Example E5 and E6 with those of Example C prepared by ExxonMobil Corporation 12 Thus, the properties of the films of inventive examples E5 and E6 appear to be better than those of the competitive films.

[0097] The films of Examples E5 and E6 and Comparative Examples C2, C7, C 12 and C 13 The water permeability (ASTM F1249-13) and permeability and oxygen permeability (ASTM D3985-17) of the films of Example E5 and E6 are lower than those of Comparative Examples C2, C7 and C 13 Thus, the membranes of inventive examples E5 and E6 provide improved protection against water and oxygen permeability compared to competitive membranes.

[0098] Table 6: Membrane process conditions

[0099] E7 E16 C2 C7 C12 C13 Die head diameter mm 160 160 160 160 160 160 Die gap mil 90 90 90 90 90 90 BUR 2.5:1 2.5:1 2.5:1 2.5:1 2.5:1 2.5:1 FLH inch 34 34 42 39 32 37 Film thickness mil 1.0 1.0 1.0 1.0 1.0 1.0 RPM rpm 50.7 50.7 54.2 51.6 50.3 42.6 rate lbs / hr 260 260 260 260 260 260 Melt temperature °F 422 422 448 438 423 413 Melt pressure 1 psi 5200 5200 6860 6380 5060 5830 Melt pressure 2 psi 4130 4130 5050 4650 3860 4390 Extrusion area 1SP °F 34 34 42 39 32 37 Extrusion area 2SP °F 34 34 38 34 33 37 Extrusion area 3SP °F 350 350 350 350 355 350 Extrusion area 4SP °F 370 370 370 370 370 370 Extrusion area 5SP °F 370 370 370 370 370 370 Extrusion area 6SP °F 370 370 370 370 370 370 Extrusion area 7SP °F 370 370 370 370 370 370 Die area 1SP °F 380 380 380 380 390 380 Die area 2SP °F 380 380 380 380 390 380 Die area 3SP °F 390 390 390 390 400 390 Die area 4SP °F 390 390 390 390 400 390

[0100] Table 7: Film physical properties

[0101]

[0102] Table 8: Test Procedure

[0103]

[0104]

[0105] Polyethylene copolymer Example E6 and Comparative Examples C2, C7, C 12 and C 13 The hot tack test and heat seal strength test were further performed as described in Table 8. Figure 2 , depicts a force versus temperature graph used during hot tack testing of Example E6 and Comparative Examples C2 and C7. Figure 3 Describe a similar graph, comparing E6 with Comparative Example C 12 and C 13 E6 and C2, C7, C 12 and C 13 Advantageously, the ethylene copolymers exhibit excellent hot tack retention in the 75-85°C range, thereby achieving a substantial degree of retention at these lower temperatures. Because sealing is a heat transfer-based mechanism, achieving robust retention at significantly lower temperatures is highly beneficial for increasing production throughput and reducing energy expenditures when making films and other articles from ethylene copolymers in accordance with the present disclosure.

[0106] See also Figure 4 , shows a graph of force versus temperature used during heat seal strength testing of Example E6 and Comparative Examples C2 and C7. Figure 5 Description of Example E6 and Comparative Example C 12 and C 13 Another graph of force versus temperature used during heat seal strength testing. Figure 4 and 5 The heat sealing strength performance of Example E6 is comparable to that of Comparative Examples C2, C7, and C 12 and C 13 In summary, then Example E6 achieves significantly better (lower temperature) processing compared to prior art solutions while achieving similar results in terms of heat seal strength.

[0107] The present disclosure may further include any one or more of the following non-limiting embodiments:

[0108] 1. An ethylene copolymer comprising from about 92.5 mol% to about 97.5 mol% ethylene derived units, and from about 2.5 mol% to about 7.5 mol% of at least one other comonomer derived units, wherein the copolymer has a molecular weight of about 0.905 g / cm 3 to about 0.912g / cm 3 and a Dow Rheology Index (DRI) / Melt Index (I2) ratio of about 0.0008 to about 0.0600.

[0109] 2. The copolymer of embodiment 1, wherein the copolymer further has a first melt index (I2) of about 0.1 to about 5.0 dg / min, as measured according to ASTM D138 (190° C. / 2.16 kg).

[0110] 3. The copolymer of embodiment 1 or 2, wherein the copolymer further has a second melt index (I21) of about 1.3 to about 90.0 dg / min, as measured according to ASTM D138 (190° C. / 21.6 kg).

[0111] 4. The copolymer of embodiments 1 to 3, wherein the density is about 0.907 g / cm 3 to about 0.911 g / cm 3 .

[0112] 5. The copolymer of embodiments 1 to 4, wherein the density is about 0.908 g / cm 3 To about 0.910g / cm 3 .

[0113] 6. The copolymer of embodiments 1 to 5, wherein the DRI / I2 ratio is from about 0.001 to about 0.060.

[0114] 7. The copolymer of embodiments 1 to 6, wherein the DRI / I2 ratio is from about 0.007 to about 0.028.

[0115] 8. The copolymer of embodiments 1 to 7, wherein at least one other comonomer is an α-olefin having 3 to 12 carbon atoms.

[0116] 9. The copolymer of embodiments 1 to 8, wherein the at least one other comonomer is 1-hexene.

[0117] 10. A method for preparing a copolymer of ethylene and at least one other comonomer, comprising: introducing ethylene and at least one other comonomer into a single reactor at a comonomer / ethylene molar ratio of about 0.02 to about 0.03; and polymerizing ethylene and at least one other comonomer at a temperature of about 76.7°C to about 81.1°C and a pressure of about 1,724 kPa to about 2,413 kPa.

[0118] 11. The process of embodiment 10, wherein the at least one other comonomer is 1-hexene.

[0119] 12. The process of embodiment 10 or 11, wherein the comonomer / ethylene molar ratio is from about 0.024 to about 0.032.

[0120] 13. The process of embodiments 10 to 12, wherein the comonomer / ethylene molar ratio is from about 0.026 to about 0.032.

[0121] 14. The process of embodiments 10 to 13, wherein the temperature is from about 76.7°C to about 80.6°C.

[0122] 15. The process of embodiments 10 to 14, wherein the temperature is from about 77.2°C to about 80.0°C.

[0123] 16. The method of embodiments 10 to 15, wherein the copolymer has a 3 to about 0.912g / cm 3 and a Dow Rheology Index (DRI) / Melt Index (I2) ratio of about 0.0008 to about 0.0600.

[0124] 17. A film made from the copolymer of embodiment 1, the film having (a) a thickness of about 1 mi l; (b) a 21 mol % oxygen permeability of about 150 to about 200 cc / 100in2 / 24hr; and (c) a hot tack seal initiation temperature of about 65°C to about 80°C.

[0125] 18. The film of embodiment 17, wherein the 21 mol% oxygen transmission rate is from about 160 to about 200 cc / 100 in2 / 24 hr.

[0126] 19. The film of embodiment 17 or 18, wherein the 21 mol% oxygen transmission rate is from about 170 to about 190 cc / 100 in2 / 24 hr.

[0127] 20. The film of embodiments 17 to 19, wherein the hot tack seal initiation temperature is from about 67°C to about 78°C.

[0128] 21. The film of embodiments 17 to 20, wherein the hot tack seal initiation temperature is from about 70°C to about 75°C.

[0129] 22. A copolymer of ethylene and at least one other comonomer prepared by the method of embodiment 10, the copolymer having: (a) about 0.905 g / cm 3 to about 0.912g / cm 3 and (b) a Dow Rheology Index (DRI) / Melt Index (I2) ratio of about 0.0008 to about 0.0600.

[0130] 23. The copolymer of embodiment 22, wherein the copolymer further has a first melt index (I2) of about 0.1 to about 5.0 dg / min, as measured according to ASTM D138 (190° C. / 2.16 kg).

[0131] 24. The copolymer of embodiment 22 or 23, wherein the copolymer further has a second melt index (I21) of about 1.3 to about 90.0 dg / min, as measured according to ASTM D138 (190° C. / 21.6 kg).

[0132] Certain embodiments and features have been described using a set of numerical upper limits and a set of numerical lower limits. It should be appreciated that, unless otherwise indicated, ranges including combinations of any two values ​​are contemplated, such as a combination of any lower limit value with any upper limit value, a combination of any two lower limits values, and / or a combination of any two upper limits values. Certain lower limits, upper limits, and ranges appear in one or more claims below.

[0133] Various terms are defined above. Where a term used in a claim is not defined above, it should be given the broadest definition persons skilled in the relevant art have given that term as reflected in at least one printed publication or issued patent. In addition, all patents, test procedures, and other documents cited in this application are fully incorporated by reference for all jurisdictions where such incorporation is permitted, provided such disclosure is not inconsistent with this application.

[0134] While the foregoing is directed to embodiments of the present invention, other and further embodiments of the invention may be devised without departing from the basic scope thereof and the scope of the invention is determined by the claims appended hereto.

Claims

1. Ethylene copolymer, comprising: 92.5 mol% to 97.5 mol% ethylene units; and 2.5 mol% to 7.5 mol% of at least one other comonomer unit, wherein the other comonomer is an alpha-olefin having 3 to 12 carbon atoms, Wherein the copolymer has: 0.905 g / cm 3 Up to 0.911 g / cm 3 density; and Dow Rheology Index DRI / Melt Index I2 Ratio of 0.007 to 0.

028.

2. The ethylene copolymer according to claim 1, wherein the copolymer further has one or both of the following: (i) a first melt index I2 of 0.1 to 5.0 dg / min, measured at 190°C / 2.16 kg according to ASTM D138; and (ii) a second melt index I21 of 1.3 to 90.0 dg / min, measured at 190° C. / 21.6 kg according to ASTM D138.

3. The ethylene copolymer according to claim 1 or claim 2, further having a molecular weight of 0.907 g / cm 3 Up to 0.911 g / cm 3 density.

4. The ethylene copolymer according to claim 3, having a molecular weight of 0.908 g / cm 3 Up to 0.910 g / cm 3 density.

5. The ethylene copolymer of claim 1 wherein the at least one other comonomer is 1-hexene.

6. The ethylene copolymer of claim 1 or claim 2, wherein the copolymer is made by a process comprising: introducing ethylene and at least one other comonomer into a single reactor in a comonomer / ethylene molar ratio of 0.02 to 0.03 as determined by measuring the moles of comonomer and ethylene in the vapor overheads of the single reactor; and Ethylene and at least one other comonomer are polymerized at a temperature of 75.4°C to 81.1°C and a pressure of 1,724 kPa to 2,413 kPa.

7. A method for preparing an ethylene copolymer according to any one of claims 1 to 6, comprising: introducing ethylene and at least one other comonomer into a single reactor in a comonomer / ethylene molar ratio of 0.02 to 0.03 as determined by measuring the moles of comonomer and ethylene in the vapor overhead of the single reactor; and Ethylene and at least one other comonomer are polymerized at a temperature of 75.4°C to 81.1°C and a pressure of 1,724 kPa to 2,413 kPa.

8. The process of claim 7, wherein the at least one other comonomer is 1-hexene.

9. A method according to claim 7 or claim 8 wherein the temperature is from 75.4°C to 80.6°C.

10. A method according to claim 7 or claim 8 wherein the temperature is from 76.7°C to 80.0°C.

11. A process for preparing an ethylene copolymer according to any one of claims 1 to 6, comprising: introducing ethylene and at least one other comonomer into a single reactor in a comonomer / ethylene molar ratio of 0.024 to 0.032 as determined by measuring the moles of comonomer and ethylene in the vapor overheads of the single reactor; and Ethylene and at least one other comonomer are polymerized at a temperature of 75.4°C to 81.1°C and a pressure of 1,724 kPa to 2,413 kPa.

12. A process for preparing an ethylene copolymer according to any one of claims 1 to 6, comprising: introducing ethylene and at least one other comonomer into a single reactor in a comonomer / ethylene molar ratio of 0.026 to 0.032 as determined by measuring the moles of comonomer and ethylene in the vapor overheads of the single reactor; and Ethylene and at least one other comonomer are polymerized at a temperature of 75.4°C to 81.1°C and a pressure of 1,724 kPa to 2,413 kPa.

13. A film made from the copolymer of any one of claims 1 to 6, the film having: (a) 1 mil thickness; (b) 150 to 200 cc / 100 in 2 Oxygen transmission rate of 100 % / 24 hr, measured at 21 mol% oxygen in accordance with ASTM D3985-17; and (c) Hot tack seal initiation temperature of 65°C to 80°C.

14. The film according to claim 13, having one or both of the following properties: (b-1) 160 to 200 cc / 100 in 2 Oxygen transmission rate of 100 % / 24 hr, measured at 21 mol% oxygen in accordance with ASTM D3985-17; and (c-1) Hot tack sealing initiation temperature of 67°C to 78°C.

15. The film according to claim 14, having one or both of the following properties: (b-2) 170 to 190 cc / 100 in 2 Oxygen transmission rate of 100 % / 24 hr, measured at 21 mol% oxygen in accordance with ASTM D3985-17; and (c-2) A heat tack sealing starting temperature of 70°C to 75°C.

Citation Information

Patent Citations

  • Grooved roller assembly for laterally stretching film

    US4368565A

  • Fluidized bed reaction systems

    US4543399A

  • Method for fluidized bed polymerization

    US4588790A

  • Fluidized bed discharge process

    US4621952A

  • Fluidized bed polymerization reactors

    US4933149A